Tenure insecurity and incremental housing development in the peri-urban interface of Ibadan, Nigeria - Moruf Alabi; Taiwo Babalola; Ayobami Popoola (Cidades, Comunidades e Território)
The increasing urbanization being experienced in African countries exacerbates their current housing needs and tenure insecurity. Despite the strictness of the formal land market in Ibadan, Nigeria, urban residents find it easier to access land from informal land market in the city, which results in incremental housing development. Based on the Self-help Theory, the study examined the contribution of tenure insecurity to the development of incremental housing in peri-urban Ibadan. A cross-sectional research design (relying on quantitative and qualitative data) was employed in the study. A total of 248 heads of household were selected from six Local Government Areas of Ibadan and each one of them was administered a structured questionnaire. Ethical protocols were followed and informed consent was obtained. The study revealed that the majority of these incremental developers was illiterate. Factors that accounted for the incremental development included fear of eviction (which is associated with tenure insecurity), high rent costs and lack of funds (as associated with income poverty). The study recommended enhancing access to secure land titles as this has multiplier-effects on housing.